Identity on q-harmonic number related to partial bell polynomials - Yan, Qinglun; Liu, Yaqing; Fan, Xiaona (Utilitas Mathematica, 2016)
In this paper, by means of the partial fraction decomposition method, we establish a general algebraic identity related to partial Bell polynomials, from which we can derive q-analog for several well-known results on harmonic number sums.